2021
DOI: 10.1093/ije/dyab217
|View full text |Cite
|
Sign up to set email alerts
|

Estimated SARS-CoV-2 infection rate and fatality risk in Gauteng Province, South Africa: a population-based seroepidemiological survey

Abstract: Background Limitations in laboratory testing capacity undermine the ability to quantify the overall burden of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection. Methods We undertook a population-based serosurvey for SARS-CoV-2 infection in 26 subdistricts, Gauteng Province (population 15.9 million), South Africa, to estimate SARS-CoV-2 infection, infection fatality rate (IFR) triangulating seroprevalence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 22 publications
(29 reference statements)
4
32
1
Order By: Relevance
“…We previously conducted a population-wide seroepidemiological survey in Gauteng that was completed on January 22, 2021. 9 We found that 19.1% of the population were anti-RBD IgG seropositive, a value that ranged from 5% to 43% across provincial sub-districts. 9 Since that time, South Africa has experienced a third wave of Covid-19 from April 7 to November 1 that was largely due to the Delta variant, which out-competed the Beta variant.…”
Section: Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…We previously conducted a population-wide seroepidemiological survey in Gauteng that was completed on January 22, 2021. 9 We found that 19.1% of the population were anti-RBD IgG seropositive, a value that ranged from 5% to 43% across provincial sub-districts. 9 Since that time, South Africa has experienced a third wave of Covid-19 from April 7 to November 1 that was largely due to the Delta variant, which out-competed the Beta variant.…”
Section: Introductionmentioning
confidence: 65%
“…This survey included the same households sampled during our previous survey, which was undertaken from November 4, 2020, to January 22, 2021, 9 nine weeks after the onset of the second wave of Covid-19 in Gauteng Province, which was dominated by the Beta variant. Details of the previous survey, including the sampling framework used, have been published 9 and are summarized in the Supplementary Methods section of the Supplementary Appendix.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations